2016
DOI: 10.22161/ijeab/1.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Abundance of Birds of Prey and Owls in Four selected Areas in South Western Nigeria

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Accipitridae with 24 species is the richest family in species number and Falconidae with 7 species. This result is in conformity with the findings of Sabo and Mohammed (2022) and Okosodo et al, (2016) who reported accipitridae as the richest family in their studies conducted at Hadejia-Nguru wetlands and South Western Nigeria respectively. It is also in agreement with Kabir (2013) who conducted his research in Bangladash and reported accipitradae as the richest family.…”
Section: Resultssupporting
confidence: 92%
“…Accipitridae with 24 species is the richest family in species number and Falconidae with 7 species. This result is in conformity with the findings of Sabo and Mohammed (2022) and Okosodo et al, (2016) who reported accipitridae as the richest family in their studies conducted at Hadejia-Nguru wetlands and South Western Nigeria respectively. It is also in agreement with Kabir (2013) who conducted his research in Bangladash and reported accipitradae as the richest family.…”
Section: Resultssupporting
confidence: 92%
“…Most nocturnal species are secretive, crepuscular and cryptic and are active at a time when access to sites is quite challenging often due to security issues. Nigeria is lacking a comprehensive inventory for nocturnal birds; however, evidence suggests a rich assemblage of owls, nightjars and other species is found across the country (Elgood et al, 1994;Okosodo et al, 2016). Some of the recorded species are African scops owl (Otus senegalensis), Standard-winged nightjar (Caprimulgus longipennis), African wood owl (Stix Woodfordii) and Western barn owl (Tyto alba) amongst others (Borrow & Demey, 2014;Elgood et al, 1994).…”
Section: Introductionmentioning
confidence: 99%